2008
DOI: 10.1021/bi7022943
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Different Five-Coordinate Soluble Guanylate Cyclase Ferrous–Nitrosyl Complexes

Abstract: Soluble guanylate cyclase (sGC), a hemoprotein, is the primary nitric oxide (NO) receptor in higher eukaryotes. The binding of NO to sGC leads to the formation of a five-coordinate ferrous-nitrosyl complex and a several hundred-fold increase in cGMP synthesis. NO activation of sGC is influenced by GTP and the allosteric activators YC-1 and BAY 41-2272. Electron paramagnetic resonance (EPR) spectroscopy shows that the spectrum of the sGC ferrous-nitrosyl complex shifts in the presence of YC-1, BAY 41-2272, or G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 39 publications
(85 reference statements)
4
47
1
Order By: Relevance
“…Previously reported resonance Raman studies demonstrated a difference between sGC-NO complexes obtained in excess or stoichiometric NO (26) and subtle changes in the EPR spectrum due to varying g 2 values (45). The addition of GTP induced a much more pronounced difference in the EPR spectra of the sGC-NO complex (45). Corroborating these findings, our EPR measurements also showed a changed line shape in the presence of GTP (supplemental Fig.…”
supporting
confidence: 79%
“…Previously reported resonance Raman studies demonstrated a difference between sGC-NO complexes obtained in excess or stoichiometric NO (26) and subtle changes in the EPR spectrum due to varying g 2 values (45). The addition of GTP induced a much more pronounced difference in the EPR spectra of the sGC-NO complex (45). Corroborating these findings, our EPR measurements also showed a changed line shape in the presence of GTP (supplemental Fig.…”
supporting
confidence: 79%
“…Consequently, a high affinity 5c NO-heme complex can be formed by displacing the proximal histidine. This idea was first proposed by Traylor, Sharma, and colleagues in the 1980-1990s (106,107,119), and is supported by the multi-step NO binding scheme proposed for cyt c¢ and by multiple electron paramagnetic resonance (EPR) and resonance Raman (rR) studies, which show that at equilibrium, the sGC-NO complex is pentacoordinate (25,28,64), as represented in Figure 8.…”
Section: Proximal Coordination Geometry and Inhibition Of Ligand Bindmentioning
confidence: 78%
“…Further detailed in vitro investigations into the involvement of additional equivalents of NO in the activation of sGC provided evidence that two distinct, spectrally identical, NO-bound states of the enzyme exist. Importantly, these states were hypothesized to be a result of either (i) two five-coordinate NO-bound species, with NO located in either the distal or proximal pocket, or (ii) a five-coordinate NO-bound heme with the additional NO equivalent modifying a cysteine residue to generate an NO-addition complex (4,(31)(32)(33)(34). The Fe II -NO structure presented here provides crystallographic evidence for the formation of proximal NO in H-NOX proteins.…”
Section: Resultsmentioning
confidence: 95%